2004
DOI: 10.1158/1078-0432.ccr-04-0875
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Insulin-Like Growth Factor-II, Insulin-Like Growth Factor-I, Insulin-Like Growth Factor-I Receptor, COX-2, and Matrix Metalloproteinase-7, Play Key Roles in the Early Stage of Colorectal Carcinogenesis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 46 publications
6
41
1
Order By: Relevance
“…In this study, the expression of total mRNA and all splicing isoforms of IGF-1 mRNA was observed in all the examined CRC and control samples. Existing data on the detection of IGF-1 mRNA vary between the absence of the transcript in CRC tissue (46), HT-29 and CaCo-2 cells (47), its detection in a proportion of cases (41-54% in CRC and 60-67% in control samples) (47)(48)(49) to its demonstration in all (100%) CRC and normal colon samples (50), which was supported by our results.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, the expression of total mRNA and all splicing isoforms of IGF-1 mRNA was observed in all the examined CRC and control samples. Existing data on the detection of IGF-1 mRNA vary between the absence of the transcript in CRC tissue (46), HT-29 and CaCo-2 cells (47), its detection in a proportion of cases (41-54% in CRC and 60-67% in control samples) (47)(48)(49) to its demonstration in all (100%) CRC and normal colon samples (50), which was supported by our results.…”
Section: Discussionsupporting
confidence: 89%
“…Nosho et al applied qPCR as we did, and demonstrated IGF-1 mRNA overexpression in ~54% of 90 human colorectal tumor tissues (49). The transcript was only faintly detected in adjacent non-tumor tissues.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…IGF-II mRNA expression was undetectable or only faintly detectable in adjacent nontumor tissue. In 6 of 7 patients with carcinomas arising in adenomas, IGF-II mRNA expression in the carcinoma was >10 times higher than in the adenoma portion of the lesion by complimentary DNA (cDNA) array analysis and IHC [14].…”
Section: Laboratory Studiesmentioning
confidence: 98%
“…In an analysis of IGF-I, IGF-II, IGF-1R, COX-2, and MMP-7 expression in 90 human colorectal tumors (63 adenomas and 27 submucosal pT1 cancers), IGF-II was also found to be the most differentially expressed gene between carcinoma and adenoma lesions [14]. Semiquantitative RT-PCR was used to detect gene expression.…”
Section: Laboratory Studiesmentioning
confidence: 99%